Reducing Hispanic Children’s Obesity Risk Factors in the First 1000 Days of Life: A Qualitative Analysis - Jennifer A. Woo Baidal; Shaniece Criss; Roberta E. Goldman; Meghan Perkins; Courtney Cunningham; Elsie M. Taveras (Journal of Obesity)
Objectives. Modifiable behaviors during the first 1000 days (conception age 24 months) mediate Hispanic children’s obesity disparities. We aimed to examine underlying reasons for early life obesity risk factors and identify potential early life intervention strategies. Methods. We conducted 7 focus groups with 49 Hispanic women who were pregnant or had children < age 24 months. Domains included influences on childhood obesity risk factors and future intervention ideas. We analyzed data with immersion-crystallization methods until no new themes emerged. Results. Themes included coping with pregnancy may trump healthy eating and physical activity; early life weight gain is unrelated to later life obesity; fear of infant hunger drives bottle and early solids introduction; beliefs about infant taste promote early solids and sugary beverage introduction; and belief that screen time promotes infant development. Mothers identified physicians, nutritionists, and relatives as important health information sources and expressed interest in mobile technology and group or home visits for interventions. Conclusion. Opportunities exist in the first 1000 days to improve Hispanic mothers’ understanding of the role of early life weight gain in childhood obesity and other obesity risk factors. Interventions that link health care and public health systems and include extended family may prevent obesity among Hispanic children.